Can teachers disrupt their professional identity and enable Children's participation? Comparing teachers' and municipal officials' work with students in democratic spaces. (November 2020) - Pinson, Halleli; Meshulam, Assaf; Michlin, Yaacov
Abstract: This paper explores how teachers conceive and facilitate children's participation in student councils, by comparing their conceptions and practices to those of municipal officials operating a municipal children's parliament. Findings from an exploratory case-study suggest that the latter, guided by citizen consultation discourse, view children as municipal citizens and treat them as adults. In contrast, teachers, guided by pedagogical ethics and protectionist developmental discourses and approaches, treat children as adults-in-the making unprepared for full participation. This divergence, we argue, offers insight into the difficulty teachers have disrupting their professional identity to enable children an equal voice in democratic spaces. This difficulty is compounded, we show, by the complexity of facilitating children's participation in the hierarchical setting of the school. Highlights: Teachers employ developmental and pedagogical discourses when facilitating students' democratic spaces. Teachers uses developmental, protectionist and pedagogical approaches to construct a 'hierarchical democracy' in schools. Municipal officials are guided by citizen consultation discourses and see children as 'municipal' citizens. The differences between teachers and municipal officials is a result of their different professional identity.